2022
DOI: 10.1371/journal.pone.0272967
|View full text |Cite
|
Sign up to set email alerts
|

Too much information: Why CDCL solvers need to forget learned clauses

Abstract: Conflict-driven clause learning (CDCL) is a remarkably successful paradigm for solving the satisfiability problem of propositional logic. Instead of a simple depth-first backtracking approach, this kind of solver learns the reason behind occurring conflicts in the form of additional clauses. However, despite the enormous success of CDCL solvers, there is still only a limited understanding of what influences the performance of these solvers in what way. Considering different measures, this paper demonstrates, q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Furthermore, it could be a worthwhile pursuit to theoretically investigate the distribution of other SLS solving paradigms, such as configuration checking solvers, e. g., CCAnr [CLS15], or WalkSAT [SKC94]. For the case of CDCL solvers we have reported results in [KLW22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it could be a worthwhile pursuit to theoretically investigate the distribution of other SLS solving paradigms, such as configuration checking solvers, e. g., CCAnr [CLS15], or WalkSAT [SKC94]. For the case of CDCL solvers we have reported results in [KLW22].…”
Section: Discussionmentioning
confidence: 99%
“…The runtime distributions of CDCL solvers was studies in [KLW22]. The authors empirically demonstrated that Weibull mixture distributions can accurately describe the multimodal distributions found.…”
Section: Previous Work On Runtime Distributionsmentioning
confidence: 99%